2012
DOI: 10.1038/ncb2629
|View full text |Cite|
|
Sign up to set email alerts
|

ERK1/2-dependent phosphorylation and nuclear translocation of PKM2 promotes the Warburg effect

Abstract: SUMMARY Pyruvate kinase M2 (PKM2) is upregulated in multiple cancer types and contributes to the Warburg effect by unclarified mechanisms. Here we demonstrate that EGFR-activated ERK2 binds directly to PKM2 I429/L431 via the ERK2 docking groove and phosphorylates PKM2 Ser37 but not PKM1. Phosphorylated PKM2 Ser37 recruits PIN1 for cis-trans isomerization of PKM2, which leads to PKM2 binding to importin α5 and nuclear translocation. Nuclear PKM2, acting as a coactivator of β-catenin, induces c-Myc expression, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
754
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(797 citation statements)
references
References 28 publications
35
754
3
5
Order By: Relevance
“…The physical association of JMJD5 with PKM2 seems to be a dominant factor. In support of this notion, Yang et al (18) showed that the intersubunit segment of PKM2 was phosphorylated by Erk2, facilitating its translocation into the nucleus. These results together suggest a mechanism whereby PKM2 can be regulated by JMJD5 binding-induced nuclear translocation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The physical association of JMJD5 with PKM2 seems to be a dominant factor. In support of this notion, Yang et al (18) showed that the intersubunit segment of PKM2 was phosphorylated by Erk2, facilitating its translocation into the nucleus. These results together suggest a mechanism whereby PKM2 can be regulated by JMJD5 binding-induced nuclear translocation.…”
Section: Discussionmentioning
confidence: 93%
“…Gao et al recently showed that the nuclear PKM2 was mainly present as a dimer (15). Notably, Yang et al (18) found that PKM2 was phosphorylated at the segment involved in multimeric assembly by Erk2, implicating that the monomeric form is crucial for the phosphorylation of PKM2 and its nuclear translocation. Thus, disruption of the tetrameric form is likely to be the key to translocate PKM2 into the nucleus.…”
Section: Jmjd5 Knockdown Reduces Cell Growth and Glycolytic Genes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the dimeric form of PKM2 which predominantly exists in cancer cells is also be reported to bias the protein kinase function toward stat3 (6). Moreover, recent studies showed that PKM2 can function as a coactivator of hypoxia-inducible factor-1␣ (HIF-1␣) and ␤-catenin under hypoxia or EGF treatment (10,11). These data indicate that PKM2 plays an important role in promoting tumor development through regulating gene transcriptions.…”
mentioning
confidence: 96%
“…For example, the mammalian pyruvate kinase PKM2 is translocated to the nucleus when the EGF receptor is activated, where it phosphorylates histone H3 instead of its usual metabolic substrate (12). A second example is the yeast homocitrate synthase, encoded by the genes LYS20 and LYS21.…”
mentioning
confidence: 99%